Reversible photoswitchable ferromagnetic thin film based on a cyanido-bridged RbCuMo complex. Issue 9 (3rd March 2021) - Ohkoshi, Shin-ichi; Shiraishi, Koki; Nakagawa, Kosuke; Ikeda, Yusuke; Stefanczyk, Olaf; Tokoro, Hiroko; Namai, Asuka
Abstract : A photoswitchable ferromagnetic thin film is developed based on a cyanide-bridged RbCuMo complex. Terahertz spectroscopy indicates that the photoreversibility is due to the flexibility of the Rb intercalated network structure. Abstract : A film-form cyanido-bridged RbCuMo complex Rb I 3/2 Cu II 7 [Mo IV (CN)8 ]31/8 ·12H2 O (RbCuMo ) was electrochemically prepared. RbCuMo has a tetragonal structure of I 4/ mmm, and Rb I is intercalated in a cyanido-bridged Cu–Mo three-dimensional network. This film exhibits a paramagnetic behavior due to Cu II ( S = 1/2). Irradiating with 473 nm light (blue laser) induces a spontaneous magnetization with a Curie temperature ( T C ) of 18 K. By contrast, irradiating the photoinduced state with 785 nm light (red laser) restores the initial paramagnetic state. The photoinduced phase transition is attributed to the change from Mo IV ( S = 0)–CN–Cu II ( S = 1/2) to Mo V ( S = 1/2)–CN–Cu I ( S = 0), which produces ferromagnetic long-range ordering between residual Cu II ( S = 1/2) and photoproduced Mo V ( S = 1/2). Although the Cs intercalated isomorph crystal lacks photoreversibility, RbCuMo shows a photoreversible phase transition. The reason for the photoreversibility in RbCuMo was investigated by terahertz time-domain spectroscopy (THz-TDS). In the THz absorption spectrum, a low-frequency phonon mode due to the vibrational mode of the intercalated Rb ion is observed at 1.11 THz (37 cm −1 ), which is lower than 1.35 THz (45 cm −1 ) of the Cs vibration mode in the Cs intercalated isomorph crystal, indicating that the Rb trapping force in RbCuMo is weaker than the Cs trapping force. The structure of RbCuMo is more flexible compared to the Cs intercalated isomorph crystal, which is considered to be the origin of the photoreversibility in RbCuMo . Such a photoreversible ferromagnetic film is useful for optical memories and photoswitchable Faraday devices.